The impact of COVID-19 on kidney transplant care - Zhang, Chi; Kodali, Lavanya; Mour, Girish; Jadlowiec, Caroline; Mathur, Amit K. (Frontiers in Medicine, 2023)
The SARS-CoV-2 virus precipitated the coronavirus 2019 (COVID-19) pandemic, which placed considerable strain on healthcare systems and necessitated immediate and rapid alterations in the delivery of healthcare. In the transplant population, COVID-19 directly impacts an inherently vulnerable population in the setting of immunosuppression and co-morbidities, but also further complicates the clinical evaluation and management of kidney transplant candidates and recipients in a strained healthcare environment being challenged by the pandemic. Many transplant centers around the world saw mortality rate spikes in organ recipients related to COVID-19, and changes in care delivery abound. This review evaluates the care of the kidney transplant patient through all phases of the process including pre-operative evaluations, perioperative care, post-transplantation considerations, and how the global pandemic has changed the way we care for our patients.